Metodologi Penunjukan Makna Ushul Fikih Dalam Menjawab Problematika Keumatan - Hesti Rahma; Fatmawati; zainal abidin (Dirosah Islamiyah, 2026)
Dalālah is an important concept in ushul fiqh that explains the relationship between wording and meaning as the basis for the process of istinbāṭ al-ahkām. This study aims to examine the concept of dalālah, the forms of indicating meaning according to the Hanafi school of thought, and its relevance in addressing contemporary community issues. This study uses a library research method with a descriptive-analytical approach through a study of ushul fiqh literature and related scientific sources. The results show that dalālah al-nash is divided into four forms, namely ibārat al-nash, isyārat al-nash, dilālat al-nash, and iqtidhā' al-nash, each of which has its own characteristics in understanding the legal content of the Qur'an and hadith. These four methods remain relevant in addressing various contemporary issues, such as sharia economics, digital transactions, health, and personal data protection. Thus, the concept of dalālah shows that Islamic law is dynamic, adaptive, and remains based on the Qur'an and Sunnah.